2008
DOI: 10.1016/j.mcn.2007.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain oscillators ticking with different clock hands

Abstract: Clock proteins like PER1 and PER2 are expressed in the brain, but little is known about their functionality outside the main suprachiasmatic clock. Here we show that PER1 and PER2 were neither uniformly present nor identically phased in forebrain structures of mice fed ad libitum. Altered expression of the clock gene Cry1 was observed in respective Per1 or Per2 mutants. In response to hypocaloric feeding, PERs timing was not markedly affected in few forebrain structures (hippocampus). In most other forebrain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
113
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 64 publications
(87 reference statements)
15
113
2
4
Order By: Relevance
“…A recent study evaluated the expression of the clock genes Per1 and Per2 using mice expressing the Venus and DsRED proteins under the control of the Per1 and Per2 promoters, respectively (110). Consistent with previous observations (102), the expression of the Per1 and Per2 transgenes was only partially overlapping in various brain regions. Detailed cellular analysis in the dentate gyrus (DG), striatum, and http://doc.rero.ch cortex revealed that Per2:DsDRED is mainly observed in cells expressing glial fibrillary acidic protein (GFAP), a marker for glial cells.…”
Section: Multiple Brain Clocks: Multiple Clock Mechanisms?supporting
confidence: 73%
“…A recent study evaluated the expression of the clock genes Per1 and Per2 using mice expressing the Venus and DsRED proteins under the control of the Per1 and Per2 promoters, respectively (110). Consistent with previous observations (102), the expression of the Per1 and Per2 transgenes was only partially overlapping in various brain regions. Detailed cellular analysis in the dentate gyrus (DG), striatum, and http://doc.rero.ch cortex revealed that Per2:DsDRED is mainly observed in cells expressing glial fibrillary acidic protein (GFAP), a marker for glial cells.…”
Section: Multiple Brain Clocks: Multiple Clock Mechanisms?supporting
confidence: 73%
“…4F). Notably, Per1 has been demonstrated to be expressed in the ARC in a manner commensurate with Gc levels (27)(28)(29)(30), and Asb4 has been found to be induced in AgRP neurons by fasting (31).…”
Section: Specific Expression Of Gr In Agrp Neuronsmentioning
confidence: 99%
“…Measures were made in the cerebellar vermis on three slices and averaged for a given brain. Measures in the hypothalamus were performed as previously described (Feillet et al, 2008). Data were expressed as relative optical density values.…”
Section: In Situ Hybridizationmentioning
confidence: 99%